2016
DOI: 10.1002/anie.201606061
|View full text |Cite
|
Sign up to set email alerts
|

Back Cover: Total Synthesis of Calophyline A (Angew. Chem. Int. Ed. 35/2016)

Abstract: Skeletal rearrangements represent a fascinating approach for generating complex architectures. In their Communication on page 10483 ff., L. Zu and co‐workers report the first total synthesis of calophyline A, by employing an aza‐pinacol rearrangement as the key strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Although there are a few examples of artificial ion channels that could be selective for ionic transmembrane translocation, the study of artificial K + channels is still in its infancy . Crown‐ether systems have been extensively used as structural elements in artificial potassium channels ,. Artificial K + channels based on resorcin[4]arene,,, the barrel‐stave model, cucurbits, and others have also been reported.…”
Section: Figurementioning
confidence: 99%
“…Although there are a few examples of artificial ion channels that could be selective for ionic transmembrane translocation, the study of artificial K + channels is still in its infancy . Crown‐ether systems have been extensively used as structural elements in artificial potassium channels ,. Artificial K + channels based on resorcin[4]arene,,, the barrel‐stave model, cucurbits, and others have also been reported.…”
Section: Figurementioning
confidence: 99%
“…Sun et al reported the fi rst a self-healing superhydrophobic coating containing fl uoroalkyl silane in its porous structure by layer-by-layer (LbL) assembly of polyelectrolyte complexes of poly(allylamine hydrochloride) and sulfonated poly(ether ether ketone) with poly(acrylic acid). [ 12 ] As Figure 13 shows, once the top layer was decomposed or scratched, the preserved fl uoroalkyl silane migrated towards the surface to heal the damaged surfaces and recover their superhydrophobicity. Also, the restoration process could be repeated many times without decreasing the superhydrophobicity.…”
Section: Restoration Of Hydrophobic Componentsmentioning
confidence: 99%
“…Unfortunately, most of these artifi cial special surfaces easily lose their special wettability in service due to mechanical abrasion, sunlight irradiation, organic contamination, or degradation, which seriously impedes their practical applications. [ 12 ] Accordingly, developing durable wetting surface materials with self-healing ability, is becoming the most intriguing topic in this fi eld in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…It involves the ruthenium-catalyzed [3+2+2] cycloaddition of diynes with 2H-azirines under mild reaction conditions to construct seven-membered fused azepine derivatives (Scheme 32, Figure 4). [49] Various typical transition-metal catalysts have been studied for such [3+2+2] cycloaddition reactions. Transition-metals such as iron, cobalt, nickel, rhodium, and iridium catalysts do not provide any [3+2+2] cycloadducts.…”
Section: Ruthenium-catalyzed [3+2+2] Cycloaddition Reactions Of Azirimentioning
confidence: 99%